Effect of Water Quality, Environmental Sanitation and Hygiene Practices on Health of School Going Children of Urban Slum Areas (Journal of Environmental Science and Natural Resources, 2015)
The study was carried out among the 246 school going children of urban slum of Tangail district and random sampling methods were applied. Slum population has been increasing in Bangladesh over the last three decades along with the growth and expansion of cities and towns.The facilities in urban slums were very much unsatisfactory due to lack of proper water supply and adequate hygiene and sanitation facilities. The good hygienic and sanitation knowledge and the practice have been found to be significantly low among the slum dwellers of Tangail district. Thewater supply and sanitation condition are improving very slowly in the urban slums of Tangail. Majority (94.7%) of the slum people use tube well water for drinking, cleaning and household purposes. The dustbin facility was the most neglected sector in these slums. Besides, Solid waste management and drainage system were totally unsatisfactory. It was observed that houses, shops, drains, roads etc. have been constructed unplanned and solid wastes were preserved on open places. Majority (58.1%) of the children did not ware sandal while going to latrine and did not cut finger nail regularly (54.5%). Most of the slum dwellers (63.4%) did not use cover for safety of the prepared food. It was observed that there was presence of pet/animal/insect in food preparation area of maximum households. Most of the people were unaware about toilet cleaning regularly. Findings of the study showed that 40.7% children were underweight, 28.9% children were stunted and 31.3% children were wasted. The child morbidity rate was high. Water quality, environmental sanitation and hygiene practices were positively correlated (r = 0 to +1) with health status of school going children. Thewater quality, environmental sanitation and hygiene practices have significant impact (p? 0.05) on the health of school going children of these slums.J. Environ. Sci. & Natural Resources, 8(1): 115-119 2015